Optimasi Komunikasi Efektif untuk Meningkatkan Keterampilan Sosial Anak Panti Asuhan Ulil Abshar Dau Sengkaling Malang: Optimizing Effective Communication to Improve the Social Skills of Children at the Ulil Abshar Dau Sengkaling Malang Orphanage - Murdiono, Murdiono (Assoeltan: Indonesian Journal of Community Research and Engagement, 2023)
The program "Effective Communication Optimization to Improve Social Skills of Children at Ulil Abshar Dau Sengkaling Malang Orphanage" aims to enhance the communication and social skills of orphaned children. Employing a holistic approach, an initial evaluation is conducted to understand individual needs, followed by training and mentoring. The training focuses on improving both verbal and non-verbal communication skills, while individual mentoring provides specific support to address emotional and social challenges. The program incorporates modern technology to broaden the communication abilities of children in the digital era. In the fifth month, there is an emphasis on understanding and appreciating cultural diversity, creating an inclusive environment. The final evaluation in the sixth month measures the progress of individuals and groups through communication skills tests and final interviews. The results include improved communication skills, positive changes in social interactions, and increased self-confidence and self-esteem among the children. The program has successfully shaped an environment that supports the holistic growth of orphaned children. Through the training and mentoring approach, the program not only strengthens communication skills but also establishes a strong foundation for the social and emotional development of children, delivering measurable positive impacts at both individual and group levels